Religion, supernaturalism, the paranormal and pseudoscience : an anthropological critique - Sidky, H., 1956- (Anthem Press, an imprint of Wimbledon Publishing Company, 2020)
"Religion, Supernaturalism, the Paranormal, and Pseudoscience" provides a comprehensive rejoinder to the challenges posed to science, scientific anthropology, evolutionary theory and rationality by the advocates of supernatural, paranormal, and pseudoscientific perspectives and modes of thought associated with the current rise of irrationalism, antiintellectualism, and emboldened religious fundamentalism and violence. Drawing upon H. Sidky's scientific anthropological background and ethnographic field research of supernatural and paranormal beliefs and practices in several cultures over three decades, the book answers several important questions: Why do humans have a proclivity for the supernatural and paranormal thinking? Why has humanity remained shackled to sets of ideas inherited from a violent past that have no basis in reality and which bestow an illusionary solace, promote bloodshed, endless cruelties and fervent hatreds, and have come at a high cost? Why have ancient superstitions been held as sacred, inviolate truths while other aspects of the archaic belief systems of which they were a part have long been discarded? Why have not humans outgrown religion and paranormal beliefs?